Resilience of vegetation cover in Southwest Mexico to the climate change effects - Santillán-Fernández, Alberto (2021)
The scenarios modeling of climate changes using geographic information systems to estimate the vegetation cover resilience is a useful tool to project future impacts and implement conservation or management strategies. We associate spatially the biodiversity of the vegetation cover of Southwest Mexico with its ability to adapt to the effects of climate change. We analysis this association estimating species richness and diversity indices, and its relationship with scenarios of future climate. Geographical records of the National Forest and Soil Inventory were obtained for eight plant communities (arboreal, shrubby, herbaceous, palm, cactus, vines, ferns, and xerophyte) distributed in Guerrero, Oaxaca, and Chiapas. The climatic projection was to 2050, with global circulation A2 models (CCCMA, HADCM3 and CSIRO average), 19 bioclimatic variables and a resolution of 2.5 minutes. Climate change scenarios were modelled with the MaxEnt algorithm and species richness, diversity index, and spatial regressions with Diva-GIS v7.5 software. The spatial regression models estimated that higher richness and species diversity, the greater resilience that the ecosystem would show. The cactus, palm, and xerophytic plant communities presented greater vulnerability to climate change. Variations in temperature seasonality turned out to be the factor that would condition its future distribution. Therefore, in conservation or management strategies, diversity should be considered as an agent of the ecosystem that cushions the negative effects of future climate.